E-Government Issues in Developing Countries Using TOE and UTAUT Frameworks: A Systematic Review - Alfiani, Husna; Kurnia Aditya, Silfa; Lusa, Sofian; Indra Sensuse, Dana; Wibowo Putro, Prasetyo Adi; Indriasari, Sofiyanti (Policy & Governance Review, 2024)
E-government, or electronic government, refers to the utilization of information and communication technology to improve and simplify the provision of government services and information to citizens, businesses, and government agencies. The adoption and implementation of e-government may be seen as an imperative for governments in developing nations. This research observes the intricacies of e-government implementation in developing countries, aiming to identify and analyze pivotal issues. By employing the preferred reporting items for systematic review and meta-analysis method, this research discovers the intricate landscape of e-government implementation. Also, utilizing the Technology-Organization-Environment and Unified Theory of Acceptance and Use of Technology frameworks, the study uncovers substantial issues rooted in organizational limitations like limited awareness and inadequate top management support. The scarcity of essential infrastructure, notably reliable internet access, exacerbates these issues, deepening the digital divide between urban and rural areas. These findings emphasize the crucial role of clear regulations and unwavering top management support. Success in technology adoption hinges on the synergy between organizational, technological, and environmental factors. This thorough investigation illuminates the complex dynamics associated with the implementation of e-government in developing countries, providing invaluable insights for policymakers, practitioners, and researchers navigating the complexities of digital governance.